2022
DOI: 10.1186/s12893-022-01511-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic mesenteric ischemia: single center analysis of open, endovascular, and hybrid surgery

Abstract: Background The aim of the study was to analyse the outcome of open surgical, endovascular, and hybrid interventions in the treatment of acute (AMI) and chronic (CMI) mesenteric ischemia. Methods Retrospective review of a cohort of mesenteric ischemia patients at a single tertiary referral center from 2015 to 2021. Primary end point was postoperative in-hospital mortality. Secondary end points were the number of bowel resections, duration of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Logistically, open approaches have resulted in quicker time to intervention [ 53 ]. While some small cohort studies have reported better outcomes for endovascular interventions [ 53 , 56 , 58 , 74 ], larger database analyses have consistently shown that these interventions are associated with improved postoperative morbidity and mortality, lower rates of in-hospital mortality, lower rates of bowel resection, decreased need for parenteral nutrition, shorter hospital stays, and lower cost compared to open surgery [ 53 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Logistically, open approaches have resulted in quicker time to intervention [ 53 ]. While some small cohort studies have reported better outcomes for endovascular interventions [ 53 , 56 , 58 , 74 ], larger database analyses have consistently shown that these interventions are associated with improved postoperative morbidity and mortality, lower rates of in-hospital mortality, lower rates of bowel resection, decreased need for parenteral nutrition, shorter hospital stays, and lower cost compared to open surgery [ 53 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Open surgical approaches vary including just surgical or hybrid approaches with laparotomy and embolectomy, endarterectomy, patch angioplasty, or bypass. 45 Endovascular First?…”
Section: Surgicalmentioning
confidence: 99%
“…10,38,[46][47][48][49][50][51][52][53] Studies have reported the 30day mortality for open surgical intervention for AMI from 32 to 42%. 45,54,55 The 30-day mortality for endovascular intervention has been shown to be lower with a study using the Swedish Vascular Registry showing a rate of 26%. 54 A single-center experience found that successful endovascular intervention had a lower mortality rate of 36% compared with surgery first, 50%, or failed endovascular with subsequent surgery, also 50%.…”
Section: Surgicalmentioning
confidence: 99%
“…Auch im Jahr 2022 wurden Ergebnisse aus einer weiteren Uniklinik publiziert. Hier lag die Mortalität bei akuter mesenterialer Ischämie „nur“ bei 29,5 %, wobei es zwischen der offenen und interventionellen Rekanalisierung keinen prognostischen Unterschied gab [ 4 ].…”
unclassified
“…In der erstgenannten Studie machten NOMI 13 % und venöse Thrombosen 4 % aus [ 1 ]. In der Arbeit aus Halle [ 4 ] wurden nur Patienten mit akutem Verschluss der A. mesenterica superior inkludiert, keine NOMI-Patienten. Dies könnte die relativ guten Ergebnisse zumindest mit erklären.…”
unclassified